The Influence of Return On Assets, Current Ratio and Debt To Asset Ratio On Financial Distress at PT Hero Supermarket Tbk Period 2008 to 2022 - Addira, Aina Salsabila; Lubis, Iman (Indonesian Financial Review, 2024)
This study aims to determine the effect of Return On Asset, Current Ratio, and Debt to Asset Ratio on Financial Distress Prediction using the Altman Z-Score Model. The research method used is an associative descriptive method with a quantitative approach. Data from the financial statements of PT Hero Supermarket Tbk 2008- 2022. Hypothesis testing using the SPSS v29 program, the results Return On Asset Tcount 2.671> Ttable 2.201 significant level 0.022 <0.05, Current Ratio Tcount -2. 822> Ttable 2.201 significant level 0.017 <0.05, Debt to Asset Ratio Tcount - 3.422> Ttable 2.201 significant level of 0.006 <0.05, obtained the results of Fcount of 6.512> Ftable of 3.59, significant level of 0.009 <0.05. Return On Asset has a significant effect, Current Ratio has a significant negative effect, Debt to Asset Ratio has a significant negative effect. Return On Asset, Current Ratio, and Debt to Asset Ratio effect on Financial Distress simultaneously.